Integration of Islamic Calligraphy into Tsangaya Education: Assessing Feasibility and Social Acceptance in Maiduguri, Nigeria - Abubakar Shettima; Mohammed Bukar; Jibrin Muhammad Habib; Abba Alhaji Bukar (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to examine the integration of Arabic calligraphy in the Tsangaya education system in Maiduguri, focusing on the perception and readiness of key stakeholders, namely teachers, students, as well as parents, and community leaders. Theoretical framework: this research focuses on cultural and religious-based education, especially on how traditional skills such as Arabic calligraphy can enrich the curriculum of non-formal Islamic education in a local context. Literature review: Relevant literature reviews may include previous research on Tsanganaya education, the learning of Arabic calligraphy in Islamic education, and the role of cultural and religious values in alternative education systems. Method: The method used in this study was a quantitative approach with data collection through a structured questionnaire distributed to 258 respondents, consisting of 45 teachers, 150 students, and 63 parents. The collected data were analyzed using descriptive statistics and inferential tests, including one-way ANOVA and Scheffé's post hoc analysis. Results: The results show that most of the respondents have a positive view of the integration of Arabic calligraphy. As many as 73.3% of teachers believe that calligraphy can add value to Tsangaya's education and are willing to take training to teach it. On the other hand, 76.6% of students expressed interest in learning calligraphy, and 80% of them thought that calligraphy skills would improve their Arabic writing skills. In addition, 84.2% of parents support integrating calligraphy in the curriculum, citing its cultural and religious significance. However, the study also identified several challenges, such as the limited number of qualified teachers (only 38.8%) and the lack of adequate teaching materials (41.9%). Implications: these findings point to the need for more strategic policies related to teacher training, curriculum adaptation, and the provision of adequate resources to support effective implementation. Novelty: this research lies in its approach that examines the integration of traditional cultural skills in the local Islamic education system, as well as the presentation of empirical data that show broad support from various stakeholders for this innovation, which has not been systematically studied in the existing literature.